DIVIDEND YIELD INVESTMENT STRATEGIES: Empirical Evidence from the Helsinki Stock Exchange 1988–2008 - Rinne, Eemeli (My University, 2009)
The purpose of this study is to investigate the effectiveness of dividend yield investment strategies in the Helsinki Stock Exchange. The strategies are based on the dividend yield anomaly which suggests that stocks with high dividend yields provide higher-than-average returns. One of the strategies utilizing the anomaly is the “Dogs of the Dow” (DoD), which calls for investing annually an equal amount of money in the ten highest-yielding components of a market index at the end of each calendar year. In addition to the standard 10-stock DoD strategy, several variations are examined. One of these is a strategy that strives to utilize the contrarian effect and the Halloween effect. The sample consists of all the Finnish companies listed in the HSE during the period 1988–2008. The performance of the strategies is analyzed on an absolute and risk adjusted bases. Risk adjustment is done using the market adjusted model and the M² measure, as well as the standard portfolio performance measures of Sharpe and Treynor. In addition, the Fama-French three-factor model is applied to remove the possible impacts of book-to-market ratio and firm size on stock returns. The results show that all of the investigated DoD strategies have provided statistically significant abnormal returns, regardless of the risk adjustment method applied. The annual abnormal returns ranged from 4.4% to 7.1%, showing that the superior returns were not merely compensation of higher risk nor caused by the value effect. The returns were also strong enough to compensate for the increased taxes and transaction costs. In addition, a clear connection between past returns, dividend yields and future returns was found, which shows that the winner-loser effect is one of the main driving forces behind the strong performance of the DoD strategies. Moreover, the study provides convincing evidence that the Halloween effect exists in the Finnish stock market.
Keywords: Dividend yield anomaly; Dogs of the Dow; Market efficiency; Winner-loser effect; Halloween effect; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|